Effect of accelerated weathering on kenaf-reinforced high density polyethylene composite - Abdul Hanan, Umar (2012)
Kenaf bast fibre reinforced high-density polyethylene (HDPE) composites were produced by compression moulding method. The composite material consists of 40% (by weight) fibres and 60% matrix. Two types of composites were fabricated from two different types of kenaf fibres; bleached and unbleached fibres were compared to investigate the effect of delignification of fibre on composites strength. Other additives such as ultraviolet (UV) stabilizer and maleic anhydride grafted polyethylene (MA-PE) as coupling agent were added into the composite material. Then, accelerated weathering test of 1000 hours (h) was conducted on the composite. The test simulates the outdoor environment which consists of heat, moisture and UV light. Mechanical properties of the composites were recorded after it was fabricated and after 200h, 400h, 600h, 800h and 1000h exposure of accelerated weathering. The mechanical performance and the weather durability of kenaf-HDPE composites were compared to neat HDPE and HDPE with UV stabilizer (HDPE+UV). The composites that used bleached fibres (K-b-HDPE) shows no significant difference with composites that used raw fibres (K-HDPE) in term of tensile strength, Young’s modulus and impact strength. However, K-HDPE composite has better flexural strength compared to K-b-HDPE. The advantage of kenaf-HDPE composites is it has better stiffness compared to HDPE or HDPE+UV. Unfortunately,the appearance of kenaf-HDPE composites becomes discoloured after weathering. Material shows the least deterioration under weathering is HDPE+UV, while neat HDPE experiences the severest damage such as rapid mechanical properties loss, chalking and micro-cracking due to weather-induced degradation. Therefore, UV stabilizers used in the composites was proven to counter UV-induced degradation. On the whole, weathering exposure on kenaf-HDPE composites enhanced with UV stabilizer and MAPE experience deterioration in term of fading and loss of mechanical properties due to weather elements such as UV light, heat and mostly because of moisture as the major contributor of degradation.